Transformasi Kurikulum: Menghadapi Tantangan Abad 21 - Neliwati Neliwati; Dwi yudha lesmana; Fitri Amelia; Muhammad Afrizal Nainggolan (FKIP, Universitas Palangka Raya, 2024)
The purpose of this study is to describe Curriculum Transformation: Facing the Challenges of the 21st Century. This type of research is a literature study research. Facing the challenges of the 21st century, education must prepare students with relevant skills and knowledge to face a changing world. Curriculum transformation, 21st Century Skills skills development, and innovative learning approaches will be key to 21st Century Learning Challenges Assessment should be related to learning and used to inspire students to learn more deeply. This will help them master the content and improve their metacognitive skills, including the ability to learn how to learn and to reflect on what has been learned.